1979
DOI: 10.1116/1.570369
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic resist for dry processing and dopant applications

Abstract: Evaporated As2S3 thin films are employed as inorganic resists in microlithography. Its sensitivity is enhanced by overcoating with a AgCl layer to form a composite. The approach combines the silver halide technology well known to the photographic industry with the newly developed chalcogenide resist technology to yield higher sensitivity and resolution. A CF4 plasma process is developed for pattern generation in these inorganic resists. Since the resist contains arsenic, a dopant for silicon device fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chalcogenide photoresists (ChP) are characterized by very high resolution, high contrast, wide spectral range of photosensitivity and the possibility to be used on both planar and non-planar substrates [1][2][3]. Additionally, the ChP possess a very high refractive index, ranging from 2.3 to 3.5, they are stable, do not need in any thermal treatment and are transparent in the infrared from 600 nm up to 12-15 lm.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide photoresists (ChP) are characterized by very high resolution, high contrast, wide spectral range of photosensitivity and the possibility to be used on both planar and non-planar substrates [1][2][3]. Additionally, the ChP possess a very high refractive index, ranging from 2.3 to 3.5, they are stable, do not need in any thermal treatment and are transparent in the infrared from 600 nm up to 12-15 lm.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, process simplification and several other advantages over the conventional selective diffusion technique can be expected. Chang et al (10) first showed that an As2S8 inorganic resist can be used as an arsenic diffusion source and demonstrated good p-n diode characteristics. However, doping of other impurities, especially p-type doping, cannot be achieved with the use of As2Ss.…”
mentioning
confidence: 99%